Interactivity and Affect in Intermedial Art: Theorizing Introverted and Extraverted Intermediality - Sluijs, Jasper; Smelik, Anneke (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2009)
The article takes two case studies of intermedial computer art, a monumental piece of interactive sound architecture, Son-O-House (2004), and an animated “open movie”, Elephants Dream (2006) as the starting point for an analysis of intermediality. The authors identify two directions in intermedial works of art: “introverted” and “extraverted”. Taking their cues from Deleuze’s notion of difference and combining them with the ideas of Dutch artist Dick Raaijmakers on the aesthetics of intermedial art, the authors claim that introverted intermediality is directed inwards, drawing self-reflexive attention to the intermedial relations of the work, while extraverted intermediality is directed outwards, engaging the user through an affective register. The concepts of introversion and extraversion point to the dynamics of intermediality and enable a more specific analysis of intermedial artworks.